Methodology and Ethics of Citation A Critique on the Book Abd-ol-Hoseyn Zarinkoub’s Lectures of Literary Criticism - Alireza Mohammadi Kalesar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Methodology of literary research in the subject of citation is in relation to research ethics. In other words, the methodological mistakes can be followed by the moral ones. This paper, in this regard, critics the book Abd–ol-Hoseyn Zarinkoub’s Lectures of Literary Criticism by Ahmad Khatami. One of the emphasized points in this article is the ambiguous boundary between the author’s speech and his sources. This ambiguity has various dimensions including equivalence of sources and equivalence of main concepts and terms. In other words, as elimination of the distinction between the author and sources in citations of this book, as if there was no difference between author’s view and sources, and even among sources. The result of this point is the naturalization in the definition of main concepts and terms. In the end, it is argued that the methodological mistake has had obvious moral consequences and faults.